Forskolin reduces fat accumulation in Nile tilapia (Oreochromis niloticus) through stimulating lipolysis and beta-oxidation - Zhang, Han; Wen, Jia-Jing; Zhang, Yun-Ni; Limbu, Samwel Mchele; Du, Zhen-Yu; Qin, Jian G.; Chen, Li-Qiao (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2019)
High fat diets are commonly used in aquaculture to reduce feed cost in Nile tilapia, but impair its lipid homeostasis. This study evaluated the role of forskolin on reducing fat accumulation in Nile tilapia (Oreochromis niloticus) by using in vitro and in vivo experiments. The use of 50 μM forskolin in vitro increased free fatty acid and glycerol release, but decreased triglyceride in adipocytes and hepatocytes. The adipose triglyceride lipase (ATGL), protein kinase cAMP-dependent type I regulatory subunit alpha (PKAR I) and other genes related to β-oxidation (peroxisome proliferator activated receptor alpha, PPARα and carnitine O-palmitoyltransferase 1, CPT1) were significantly up-regulated. After feeding a high-fat diet for six weeks, O. niloticus were fed with 0 (control), 0.5 and 1.5 mg/kg forskolin for two weeks to determine whether forskolin could reduce fat accumulation in vivo. Fish fed the two levels of forskolin decreased significantly the hepatosomatic and mesenteric fat indices. The total lipid in the whole fish and liver together with the serum glycerol content were lower in fish fed on forskolin than in the control. The fish fed on forskolin diets exhibited smaller areas of lipid droplets in adipose and liver tissues. Lipolysis related genes (ATGL, hormone-sensitive lipase, HSL; monoacylglycerol lipase, MGL; and protein kinase cAMP-activated catalytic subunit, PKAC) and β-oxidation genes (PPARα; fatty acid binding protein 1, FABP1; and CPT1) in the adipose were up-regulated. Similarly, in the liver lipolysis genes such as ATGL and PKAR I and β-oxidation genes (PPARα, FABP1, CPT1 and acyl-CoA oxidase, ACO) showed an increasing trend with the increase of forskolin doses. This study indicates that forskolin can reduce fat accumulation in the adipose and liver by stimulating lipolysis and β-oxidation in O. niloticus. •Forskolin supplementation in the diet reduced fat accumulation in Nile tilapia.•Lipolysis and β-oxidation in adipocytes and hepatocytes were stimulated by 50 μM forskolin in vitro.•The oral doses of 0.5 and 1.5 mg/kg forskolin reduced fat in the liver and whole fish.•Forskolin up-regulated the expression of genes relevant to lipolysis and β-oxidation.